SOME OF DESMIDIAL ALGAE AT NATHSAGAR WATER BODY, PAITHAN- MAHARASHTRA - G. BANDGAR, SHRIDEVI; P. B. PAPDIWAL, (The Bioscan, 2013)
In this paper the Desmidial Algae, belonging to Class Chlorophyceae, from Nathsagar water reservoir, Paithan (Maharashtra) have been described. These algae belong to four genera viz., Micrasterieas, Euastrum, Cosmarium and Staurastrum. As a part of study of Plant diversity, algal diversity of Nathsagar water body was carried out from March 2011 to January 2013. Algal samples were collected from different sites of water body.